2011
DOI: 10.1039/c0nr00761g
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-coordinated metal complexes precede the formation of liquid amorphous mineral emulsions of divalent metal carbonates

Abstract: During the mineralisation of metal carbonates MCO3 (M = Ca, Sr, Ba, Mn, Cd, Pb) liquid-like amorphous intermediates emerge. These intermediates that form via a liquid/liquid phase separation behave like a classical emulsion and are stabilized electrostatically. The occurrence of these intermediates is attributed to the formation of highly hydrated networks whose stability is mainly based on weak interactions and the variability of the metal-containing pre-critical clusters. Their existence and compositional fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 59 publications
2
118
0
7
Order By: Relevance
“…They describe a non-classical nucleation mechanism through the existence of stable prenucleation clusters in subsaturated calcium carbonate solutions. Such clusters are discussed by Raiteri and Gale [24], Gebauer and Cölfen [25], and were experimentally verified by ultracentrifuge experiments, cryo-TEM and mass spectrometry [23][24][25][26]. It has been found that they remain hydrated [24].…”
Section: Magnetic Water Treatmentmentioning
confidence: 79%
See 1 more Smart Citation
“…They describe a non-classical nucleation mechanism through the existence of stable prenucleation clusters in subsaturated calcium carbonate solutions. Such clusters are discussed by Raiteri and Gale [24], Gebauer and Cölfen [25], and were experimentally verified by ultracentrifuge experiments, cryo-TEM and mass spectrometry [23][24][25][26]. It has been found that they remain hydrated [24].…”
Section: Magnetic Water Treatmentmentioning
confidence: 79%
“…Whereas their structure has not been determined yet, molecular dynamics simulations [27] describe them as disordered, hydrated flexible ionic polymers or DOLLOPs (dynamically ordered liquid like oxyanion polymers). They can aggregate into larger particles (up to about 100 nm) and form a liquid emulsion [26]. Coey [21] describes how a magnetic field gradient can act on the DOLLOPs, which could account for the so-called "magnetic memory" of water.…”
Section: Magnetic Water Treatmentmentioning
confidence: 99%
“…6 These not only provide the opportunity to perform hundreds of experiments very quickly, but the small reaction volume is such that the majority of droplets do not contain impurities; those that do generate outlying data points and can in principle be excluded. To this end, levitated droplets 7,8 and droplets created using automated dispensing systems 9-11 have previously been used to study homogeneous nucleation and to facilitate rapid screening of crystallisation conditions. Arrays of picolitre droplets formed on patterned self-assembled monolayers (SAMs) in contrast have provided an opportunity to study heterogeneous nucleation in confined volumes.…”
Section: Introductionmentioning
confidence: 99%
“…The LACC develops from pure, neutral, and saturated calcium bicarbonate solution crystallizing homogeneously in acoustic levitation [20]. These characteristic intermediates behave like a classical emulsion and are stabilized electrostatically [31]. Extended studies with additives resulted in destabilization phenomenon of LACC precursor using lysozyme, whereas the glycoprotein ovalbumin stabilizes this transient state, which carries a negative surface charge, and prevents undirected mineralization of the eggshell [32].…”
Section: Introductionmentioning
confidence: 99%
“…Our group pioneered a few years ago with the first time resolved in situ XRD experiments providing a continuous set of XRD patterns during a crystallization process [17,18,30]. In one of the early experiments, the non-classical crystallization pathway of calcium carbonate system involving a liquid/liquid phase separation and an emulsified of a highly hydrated liquid amorphous calcium carbonate (LACC) was investigated [20,31]. The LACC develops from pure, neutral, and saturated calcium bicarbonate solution crystallizing homogeneously in acoustic levitation [20].…”
Section: Introductionmentioning
confidence: 99%